The structure of canopy flow field - Kawatani, Takeshi, author; Meroney, Robert N., author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1968)
A model study of canopy flow over high roughness elements was carried out in the Army Meteorological Wind Tunnel at Colorado State University using roughness consisting of pegs 9 cm high and 0.48 cm in diameter arranged in four patterns. The mean velocity and the turbulence intensity were measured within and above the roughness elements. Empirical expressions derived from field measurements for mean velocity profiles, turbulent velocity, and turbulence intensity were used to examine the data obtained in this model study. The logarithmic profile was adapted to analyze the data of mean velocity above the canopy. In this analysis, the friction velocity and the roughness parameter were calculated from the mean velocity profiles and related to the density of roughness elements to show the effects of roughness density on the flow field. The growth of the internal boundary layer was estimated from the mean velocity profiles and the turbulence intensity. The results of estimation were compared with semi-empirical equations. Although the coefficient of anisotropy above the canopy in this model study is larger than that in the field, the model study gave data about the turbulent flow field similar to the field data. Hence, this model was verified to be suitable for the study of diffusion.
CER67-68TK66.
August 1968.
Prepared under U.S. Army Research Grant DA-AMC-28-043-65-G20.
Keywords: Micrometeorology